Legal regulation of land reform during the period of the Ukrainian Central Rada - Ukhach, Vasyl (Actual problems of law (Aktual’ni problemi pravoznavstva), 2024)
An analysis of the genesis of legislative regulation of one of the key issues of Ukrainian liberation struggles of the 1920s – the land issue has been conducted. The aim of the article is to explore certain segments of the genesis of legal regulation in resolving the land issue by the Ukrainian Central Rada and the governments of the «first» Ukrainian People’s Republic. It is argued that alongside the problems of national liberation and the establishment of the Ukrainian state, the effective resolution of agrarian issues not only allowed the eternal dream of the Ukrainian peasant-farmer to be the master of his own land to be realized, but also provided electoral support to Ukrainian political forces. Conclusions are drawn that the land legislation of the period of the Ukrainian Central Rada and the «first» Ukrainian People’s Republic constantly underwent changes under the influence of sharp internal and external factors. A characteristic feature of revolutionary events in Ukraine was the close interconnection of national and social moments. The declaration of the land as the property of the working people, even purely declarative, divided Ukrainian society into opposing camps. The socialization of land contradicted the Ukrainian national mentality, the ideal of which had always been the free farmer working on his own land. The indecision, postponement, and polyphony of approaches by the leaders of the Ukrainian Central Rada to resolving the land issue undermined trust in it daily, drastically narrowing its electoral base. The main problem – of people, land, and freedom – remained unresolved.